Regulation of carboxylesterase‐2 expression by p53 family proteins and enhanced anti‐cancer activities among 5‐fluorouracil, irinotecan and doxazolidine prodrug. (25th March 2013) - Xiao, Da; Yang, Dongfang; Guo, Liangran; Lu, Wei; Charpentier, Margaret; Yan, Bingfang
<x xml:space="preserve">Abstract</x> Background and Purpose For four decades, 5‐fluorouracil (5‐FU) has been a major anti‐cancer medicine. This drug is increasingly used with other anti‐cancer agents such as irinotecan. Irinotecan and many others such as PPD (pentyl carbamate of p‐aminobenzyl carbamate of doxazolidine) require activation by carboxylesterase‐2 (CES2). 5‐FU, on the other hand, reportedly induces CES2 in colorectal tumour lines. The aims of this study were to determine the molecular basis for the induction and to ascertain interactive cell‐killing activity between 5‐FU and ester prodrugs. Experimental Approach Colorectal and non‐colorectal lines and xenografts were treated with 5‐FU and the expression of CES2 was determined. Cell‐killing activity of irinotecan and PPD were determined in the presence or absence of CES2 inhibitor. Several molecular experiments were used to determine the molecular basis for the induction. Key Results Without exceptions, robust induction was detected in cell lines expressing functional p53. High‐level induction was also detected in xenografts. 5‐FU pretreatment significantly increased cell‐killing activity of irinotecan and PPD. Molecular experiments established that the induction was achieved by both transactivation and increased mRNA stability through p53. Either p63 or p73, functionally related to p53, did not support the transactivation. Conclusions and Implications The results in this study suggest that FOLFIRI, a common regimen combining irinotecan and 5‐FU, should switch the dosing sequence, namely from 5‐FU to irinotecan, to enhance hydrolytic activation of irinotecan. This modified order likely reduces the dose of anti‐cancer agents, thus minimizing overall toxicity. The results also conclude that p53 family members act differently in regulating gene expression.